AB0469 Evolution of Anthropometric Profile and Habit Food after 10 Years in Systemic Lupus Erythematosus Patients. (15th July 2016) - Souza, L.S.; Calzza, J.; Cassol, Έ.; Xavier, R.M.; Monticielo, O.
Abstract : Background: Systemic Lupus Erythematosus (SLE) is an autoimmune inflammatory disease that affects various organs and systems. Cardiovascular disease is a common complication and is associated with factors inherent to the SLE and environmental factors such as overweight and poor eating habits. In addition, obesity has been speculated as a contributing factor to the onset and progression of autoimmune diseases. Objectives: Evaluate the anthropometric profile and food habit after 10 years of follow-up of a group of patients with SLE and identify possible association with chronicity index and disease activity. Methods: We evaluated 55 patients with SLE in two moments with an interval of 10 years, coming from a care referral center for SLE in Hospital de Clínicas de Porto Alegre, Brazil. For chronicity and activity was used Systemic Lupus International Collaborating Clinics (SLICC) index and Systemic Lupus Erythematosus Disease Activity Index (SLEDAI), respectively. Body Mass Index (BMI), Body Fat Percentage (BFP) and waist circumference (WC) were the anthropometric data collected in accordance with the standards of the World Health Organization (WHO). The total cholesterol, LDL, HDL and triglycerides were performed as routine care. The study was approved by the Ethics Committee of the Universidade Federal of Rio Grande do Sul (UFRGS) and all patients who agreed to participate in the study met the consent and informed. Results: Conclusions: Our study revealed a worsening in the lipid profile and a higher concentration of abdominal fat in patients with SLE after 10 years of follow-up, although diet has remained stable. Factors related to disease or treatment may have influenced these results, but were not assessed in this study. These findings serve as a warning to us take better care of the nutritional status and lipid profile of our patients. References: The epidemiology of atherosclerotic cardiovascular disease among patients with SLE: A systematic review. S.R. Schoenfeld et al./Seminars in Arthritis and Rheumatism 43 (2013) 77–95. Obesity in autoimmune diseases: Not a passive bystander. M. Versini et al./Autoimmunity Reviews 13 (2014) 981–1000. Factors associated with damage accrual in patients with systemic lupus erythematosus: results from the Systemic Lupus International Collaborating Clinics (SLICC) Inception Cohort Bruce IN, et al. Ann Rheum Dis 2014;0:1–8. doi:10.1136/annrheumdis-2013-205171 World Health Organization. Physical status: the use and interpretation of anthropometry. Report of a WHO Expert Committee. Geneva: World Health Organization;1995 (WHO Technical Report Series, no. 854). Disclosure of Interest: None declared